Qualitative Inquiry and the Self-Realization of Psychological Science. (February 2014) - Freeman, Mark
It is commonly assumed that qualitative inquiry in psychology, whatever its virtues, does not lend itself as readily to the development of (real, true) scientific knowledge as those ostensibly more objective approaches found in quantitative inquiry. At the same time, it is also assumed that qualitative inquiry aspires to be more faithful to "real-life" phenomena in all of their richness. The situation is thus a paradoxical one: Despite the fact that qualitative inquiry seeks to uphold what is, arguably, the first and most fundamental responsibility of scientific knowing—fidelity to the phenomena—it continues to be questioned, if not condemned, for falling short of the scientific mark. Bearing this paradox in mind, it is argued herein that the social sciences in general, and psychology in particular, have operated with a problematically restrictive view of science and that qualitative inquiry can be instrumental in the fashioning of a more inclusive, capacious, and indeed adequate view. A corollary argument is that it can do so to the degree that it becomes more artful in at least a portion of its work. The paradoxical promise of qualitative inquiry thus lies in its potential to artfully re-imagine both the meaning and the practice of psychological science.